2014
DOI: 10.1038/cddis.2014.515
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Kaposi’s sarcoma-associated herpes virus microRNAs in sepsis and surgical trauma

Abstract: Once a patient is in septic shock, survival rates drop by 7.6% for every hour of delay in antibiotic therapy. Biomarkers based on the molecular mechanism of sepsis are important for timely diagnosis and triage. Here, we study the potential roles of a panel of cellular and viral miRNAs as sepsis biomarkers. We performed genome-wide microRNA (miRNA) expression profiling in leukocytes from septic patients and nonseptic controls, combined with quantitative RT-PCR in plasmas from two cohorts of septic patients, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 29 publications
3
77
1
Order By: Relevance
“…Finally, to demonstrate that miR-29a binds directly to TLR8 we transfected human DCs with Flag-TLR8 plasmid. The transfected cells were incubated with miR-29a or miR-155 or U6 (negative controls) (39) and immunoprecipitation and RNA-IP was performed 72 hrs post-transfection. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to demonstrate that miR-29a binds directly to TLR8 we transfected human DCs with Flag-TLR8 plasmid. The transfected cells were incubated with miR-29a or miR-155 or U6 (negative controls) (39) and immunoprecipitation and RNA-IP was performed 72 hrs post-transfection. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Tudor et al observed that two KSHV miRNAs are up-regulated in the blood of septic and postoperative patients (52). It is well known that Kaposi Sarcoma (KS) is associated with immunosuppressive states, especially that of AIDS (59).…”
Section: The Mechanisms Behind the Complications The Mechanisms Behinmentioning
confidence: 99%
“…The most intriguing fact was that 2 of these miRNAs are viral miRNAs (miR-K-12-10b and miR-K-12-12*) belonging to the genome of Kaposi sarcoma-associated herpesvirus (KSHV). These two miRNAs are upregulated in sepsis (52). In a review article Benz et al presents all circulating miRNAs discovered and recommended as sepsis biomarkers (53).…”
Section: The Mechanisms Behind the Complications The Mechanisms Behinmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Dr. George A. Calin (University of Texas MD Anderson Cancer Center, Houston, TX) presented his findings that cellular and Kaposi’s associated Herpesvirus (KSHV) miRNAs are differentially expressed in the plasma of sepsis and early postsurgical patients. In particular, virally encoded miR-K-10b and miR-K-12-12* expression was increased immediately following surgery, suggesting that the levels of the KSHV’s miRNAs in plasma can be used as biomarkers of sepsis(34). He also discussed how a novel lncRNA, CCTA2, transcribed from the 8q24, promoted metastasis and chromosomal instability in colon cancer(35).…”
mentioning
confidence: 99%